Modelagem da qualidade da água da bacia Olhos d’Água em Feira de Santana - BA: geoprocessamento aplicado à análise de impactos ambientais - Carelli, Liamara (2011)
This study aimed at the analysis of the water quality and the determination of environmental impacts of effluent discharge in a watershed. For this purpose, we delimited as study area the Olhos D’Água basin that is inserted in the river Jacuípe basin, in the municipality of Feira de Santana, Bahia state. Along its route, the Olhos D’Água basin receives domestic sewage and solid wastes due to its crossing of the city urban area. The methodology consisted in the analysis of chemical, physical and biological indicators of water quality, as well as on-site observation of the problems in the study area, documented through photographs over ten collection points. The data were analyzed temporally and spatially, and they are also used in the construction of two indices of water quality, the Water Quality Index of Bascarán (IQAB) and the Objective Index of Water Quality (IQAOBJ). We found several changes in the quality of the water in Olhos D'Água throughout its drainage area. Taking the limits established by CONAMA Resolution 357/2005 for class 3 as parameters, median values were considered inadequate for the variables Dissolved Oxygen (in 7 out of 10 points), B.O.D. (in 9 of 10 points), color (two points) and total and fecal coliforms (10 and 3 points respectively). Even the median of each parameter being within tolerable limits, there were many peaks of values out of bounds. The number of fecal coliforms in the water basin reach values of order up to 2 million bacteria per 100 ml in the most critical points, including alarming figures even in the discharge zone. These results lead to the conclusion that the Olhos D’Água basin has a high level of degradation of its waters and represents a health risk for the population living around it, including the population that uses water near the confluence between the Olhos D’Água creek and Jacuípe river.